KOMUNIKASI INKLUSIF DALAM PELAYANAN PELANGGAN MULTIKULTURAL PADA BISNIS KULINER GUNA MENDUKUNG PENGEMBANGAN PARIWISATA - Aisyah, Nabilah Azzah; Callista, Amanda; Zalukhu, Sarianto; Pranata, Muhamad Aqsa; Maldin, Siska Amelia (JURNAL MATA PARIWISATA, 2025)
This study aims to examine the concept and practice of inclusive communication in serving multicultural customers in the culinary business through a literature review approach. Using a library research method, data were collected from various sources such as books, journals, articles, and documents related to cross-cultural communication and culinary business. Thematic and comparative analysis techniques were employed to identify effective communication strategies and the challenges faced by culinary business actors when interacting with customers from diverse cultural backgrounds. The findings reveal that inclusive communication plays a significant role in enhancing customer satisfaction and creating a harmonious business environment. Cross-cultural communication training and awareness of cultural diversity are key factors in the successful implementation of inclusive communication within multicultural culinary businesses. This study provides theoretical and practical contributions to the development of adaptive and inclusive communication strategies in the culinary sector.